Epidemiologia de infecção por Candida spp. relacionada a corrente sanguínea, ocorridas no Hospital de Clínicas de Uberlândia - Alves, Priscila Guerino Vilela (2018)
Fungal infections have become a major challenge in hospitals and the number of episodes of fungal infections of the bloodstream (BSI) has increased since the early 1990s. Candida spp. remains the most common cause of invasive fungal infections. Over the past 20 years, there has been improvement in diagnostic procedures, development and commercialization of new antifungal agents and implementation of strategies to prevent candidemia, however, the incidence of candidemia has increased and mortality rates remain high (40-60%). The objective of this study was to analyze the occurrence of Candida species related to candidemia in the Hospital of Clinics of Uberlandia from January 2009 to December 2016. Patients with positive blood culture for Candida spp. collected after 48 hours of hospitalization. Patients with candidemia were divided into two groups: Period 1: 2009-2012 and Period 2: 2013-2016. This study analyzed the patient's medical records from an analysis form for demographic, clinical and outcome information (discharge and / or death). A total of 335 patients with candidemia were included. The risk factors associated with mortality by periods were: hospitalization at the Medical Clinic (period 1, p = 0.01), neoplasia (period 2, p = 0.01), age> 51 years (both periods, p = , P = 0.01), mechanical ventilation (period 1, p = 0.03, period 2, p = 0.01), orotracheal intubation (both periods, p = 0.02), hemodialysis p = <0.01) and use of corticosteroids (period 2, p = <0.01). The most frequent species were Candida albicans (43.1% and 42.7%), C. tropicalis (25.0% and 18.2%), C. parapsilosis (15.0% % and 17.7%) C. krusei (6.9% and 9.9%) and C. glabrata (3.8% and 4.2%). In conclusion, the multiple logistic regression analysis revealed that the independent risk factors associated with mortality were: age> 51 years, neoplasia, hemodialysis, use of mechanical ventilation, orotracheal intubation and corticosteroids. The incidence rates of candidemia confirm those found in other tertiary care hospitals in Brazil, with Candida albicans being the most frequent.